Evaluation of XYZ Sme Compensation With Determination of Position Grade Using Hay Job Evaluation Methods - Faiza Nur Aulia; Hasna Nadiyah Banafsaj Sudaryono; Arina Salsabila Santoso; Sindhy Larasati; Muhammad Ilham Pratama (International Journal of Social Service and Research, 2021)
In an organization or company, determining the differences and grading between positions is needed to determine the obligations between positions and the level of compensation. The level or grade of the position will affect how much compensation is given by the company to its employees and also reflects the knowledge, skills, and responsibilities of employees at each level. The object of research from this scientific journal is UKM XYZ which is engaged in food processing in accordance with Law Number 20 of 2008 concerning Micro, Small and Medium Enterprises (MSMEs). UKM XYZ is an UKM that has been established since 2004 and is located in Lembang, West Bandung Regency, West Java. The research was conducted to evaluate the salary system in UKM XYZ compensation to be more fair and effective for each employee using Job Value & Grading basis and salary mapping system with Adhered and Overlapping. The data used in this study are primary and secondary data obtained through online systems such as conducting interviews through Zoom Meetings, distributing questionnaires through Google Forms, analyzing salary attachments, and conducting various literature studies through several journals. In this study, the weighting criteria used were based on the Hay System criteria, namely Know-How, Problem Solving, and Accountability. This research is a quantitative and qualitative research by describing the job grade system in compensation run by UKM XYZ